Estimating investment equations in imperfect capital markets - Silke Hüttel; Oliver Mußhoff; Martin Odening; Nataliya Zinych (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
Numerous studies have tried to provide a better understanding of firm-level investment behaviour using econometric models. The model specification of more recent studies has been based on two main approaches. The first, the real options approach, focuses on irreversibility and uncertainty in perfect capital markets; of particular interest is the range of inaction caused by sunk costs. The second, the neo-institutional finance theory, emphasises capital market imperfections and firms' released liquidity constraints. Empirical applications of the latter theory often refer to linear econometric models to prove these imperfections and thus do not account for the range of inaction caused by irreversibility. In this study, a generalised Tobit model based on an augmented q model is developed with the intention of considering the coexistence of irreversibility and capital market imperfections. Simulation-based experiments allow investigating the properties of this model. It can be shown how disregarding irreversibility reduces effectiveness of simpler linear models.
Keywords: D81; D92; C51; 330; q model; uncertainty; capital market imperfections; generalised Tobit model; Investitionsfunktion; Tobin's Q; Tobit-Modell; Finanzmarkt; Unvollkommener Markt; Theorie